“I do not Feel Included”: Teachers’ Experiences of Workplace Inclusion at Higher Education - Iram Parveen. Muhammad Uzair-ul-Hassan. Ume Aimen, (JIE, 2024)
Workplace inclusion is believed to be an attractive and professional environment in which equality prevails for all members and they feel importantly involved and interactive with leaders during decisionmaking process along with availability of all information in theinstitution. The sole objective of the study was to explore the challenges being faced by teachers for workplace inclusion at higher education. Qualitative data were collected from 12 public sector university teachers from Punjab through a self-developed interview protocol comprised of 9 open-ended questions.